Impact dynamics of the L chondrites' parent asteroid. (24th February 2022) - Ciocco, Marine; Roskosz, Mathieu; Doisneau, Béatrice; Beyssac, Olivier; Mostefaoui, Smail; Remusat, Laurent; Leroux, Hugues; Gounelle, Matthieu
Abstract: The dynamics of collisional events have been studied for three highly shocked L chondrites (Tenham, Sixiangkou, and Acfer 040). Crystal growth rates of high‐pressure polymorphs of olivines and pyroxenes and diffusion‐driven redistribution of Mn, Ca, Fe, and Na associated with these polymorphic transitions were studied independently. These two approaches were then applied on the same samples, and for meteorites that underwent different collisional histories. The relevance of the use of pyroxene polymorphs (e.g., akimotoite) is demonstrated. Combined analysis of the exact same ringwoodite and akimotoite crystals by scanning transmission electron microscopy (STEM) and NanoSIMS demonstrate that while STEM has a better lateral resolution, the 40 nm maximum resolution of the NanoSIMS is sufficient to distinguish and analyze diffusion profiles. With STEM chemical and structural information concerning the nucleation mechanisms of ringwoodite and akimotoite, the concentration profiles derived from NanoSIMS images were used to derive the shock pulse duration and impactor size for these three meteorites. The two approaches (crystal growth kinetics and elemental diffusion) provide comparable durations assuming that diffusion coefficients are carefully selected. We obtain shock time scales of 1, 7, and 4 s for Tenham, Sixiangkou, and Acfer 040, respectively. Corresponding impactor sizes are also calculated, and the results point toward either (i) an early separation of the L chondrites from the parent body, and secondary impacts resulting in the observed meteorites or (ii) the meteorites all originate from different depths in the parent body.